OPTIMALISASI MANAJEMEN STRATEGI PADA PONDOK PESANTREN KHADIMUL UMMAH DI KAMPUNG BARU DESA LEMBANNA KECAMATAN KAJANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Optimizing strategy management at the Khadimul Ummah Kajang Islamic Boarding School plays an important role in the development of pesantren by implementing stages of strategy management, starting from strategy formulation, strategy implementation, to strategy control. There are several supporting and inhibiting factors in optimizing strategy management at this boarding school. Supporting factors are the existence of Islamic boarding schools that received appreciation from the surrounding community and the achievements obtained by the students who were able to demonstrate the existence of the Islamic Boarding School Khadimul Ummah Kajang. The inhibiting factors are the lack of teaching staff and the lack of facilities and infrastructure in the boarding school environment.